2023
DOI: 10.3390/en16052222
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Energy and Exergy of Geothermal Organic Rankine Cycle

Abstract: In this study, modeling and thermodynamic analysis of the combined double flash geothermal cycle generation was conducted using zeotropic fluid as the working fluid in the Organic Rankine Cycle (ORC). The analysis was performed based on the first and second laws of thermodynamics. Hexane, cyclohexane, isohexane, R245fa, and R236ea exhibit good performance at higher temperatures. In this study, three fluids—hexane, cyclohexane, and isohexane—were used. First, the model results for the pure fluids were compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The results indicated that using zeotropic mixtures is a promising approach to enhancing the economics of geothermal ORC systems. Alghamdi et al 28 analyzed the double flash geothermal cycle using zeotropic fluid in the ORC, evaluating its thermodynamics based on the first and second laws. Hexane, cyclohexane, and isohexane were identified as effective fluids for higher temperatures.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results indicated that using zeotropic mixtures is a promising approach to enhancing the economics of geothermal ORC systems. Alghamdi et al 28 analyzed the double flash geothermal cycle using zeotropic fluid in the ORC, evaluating its thermodynamics based on the first and second laws. Hexane, cyclohexane, and isohexane were identified as effective fluids for higher temperatures.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Transcritical cycle configurations achieved the highest energy efficiency (17.7%), while isopentane performed better than isobutane and R245ca for the high-temperature geothermal reservoir. Alghamdi et al [20] studied the energy and exergy performance of a double-flash cycle with zeotropic mixtures for power generation from a high-temperature (200 • C) geothermal source. The highest net power and the lowest exergy dissipation were obtained with a mixture of cyclohexane and R236ea, which provided the best thermal match with the geothermal fluid.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Solar energy has been identified as the most abundant source of energy, [5][6][7] and it has been estimated that the amount of solar energy entering the earth for 1 h is more than the annual energy consumption of world societies. [8][9][10][11] Currently, solar energy provides part of the energy needed by advanced countries in two forms: electrical energy through photovoltaic systems and thermal energy using solar collectors. [12][13][14] Among the types of solar systems technology, the linear parabolic collector has been widely accepted due to the fact that it can produce high temperatures for heating and cooling, , it needs less space to reflect sunlight in the focal area, and various ways have been proposed to increase the efficiency of this technology.…”
mentioning
confidence: 99%